The methodology for assessing interest-rate policy rules: a reply - John Smithin (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
This note is a brief reply to , who has been critical of the conceptual foundations and methodology in a discussion of the impact of different interest rate policy rules on inflation in . The reply concludes that the case for a 'zero real policy rate of interest' (ZRPR), rather than a 'zero interest rate policy' (ZIRP), emerges unscathed.
Keywords: B22; E43; E52; E58; 330; ZRPR; ZIRP; real interest rate rules; inflation instability; income distribution